2020
DOI: 10.1002/art.41105
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prospective Study of the Efficacy and Safety of Combined Immunosuppressive Therapy With High‐Dose Glucocorticoid, Tacrolimus, and Cyclophosphamide in Interstitial Lung Diseases Accompanied by Anti–Melanoma Differentiation–Associated Gene 5–Positive Dermatomyositis

Abstract: Objective Interstitial lung disease (ILD) accompanied by anti–melanoma differentiation–associated gene 5 (anti–MDA‐5)–positive dermatomyositis (DM) is often rapidly progressive and associated with poor prognosis. Because there is no established treatment, we undertook this study to prospectively evaluate the efficacy and safety of a combined immunosuppressive regimen for anti–MDA‐5–positive DM patients with ILD. Methods Adult Japanese patients with new‐onset anti–MDA‐5–positive DM with ILD (n = 29) were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
168
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(212 citation statements)
references
References 44 publications
7
168
1
2
Order By: Relevance
“…More importantly, the prognosis can be extremely poor due to high incidence of rapidly progressive interstitial disease (RP‐ILD) in these patients. The condition requires prompt diagnosis and early initiation of aggressive immunosuppressive therapy to improve prognosis . We report two interesting patients of Polynesian descent, presenting with MDA5‐associated DM, with fatal outcome in one.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…More importantly, the prognosis can be extremely poor due to high incidence of rapidly progressive interstitial disease (RP‐ILD) in these patients. The condition requires prompt diagnosis and early initiation of aggressive immunosuppressive therapy to improve prognosis . We report two interesting patients of Polynesian descent, presenting with MDA5‐associated DM, with fatal outcome in one.…”
mentioning
confidence: 98%
“…Anti‐melanoma differentiation‐associated gene 5 antibody‐associated dermatomyositis (MDA5‐associated DM) is a rare subgroup of idiopathic inflammatory myositis, presenting with cutaneous features of classical dermatomyositis (DM), but no or minimal involvement of the proximal muscles. Numerous cases of DM associated with MDA5 antibodies have been described in the literature, emphasising the need for early diagnosis in this rare entity which may be overlooked due to substantially different clinical presentations . More importantly, the prognosis can be extremely poor due to high incidence of rapidly progressive interstitial disease (RP‐ILD) in these patients.…”
mentioning
confidence: 99%
“…Typically, RP-ILD requires initial high-dose glucocorticoid combined with other immunosuppressive agents such as cyclophosphamide, rituximab, and calcineurin inhibitors (including cyclosporin A and tacrolimus) [16,17]. A recent multicenter prospective study demonstrated that a combination of immunosuppressive drugs, consisting of high-dose glucocorticoid, tacrolimus, and intravenous cyclophosphamide, was significantly more effective in patients with anti-MDA5-positive DM with ILD than step-up treatment (high-dose glucocorticoid and stepwise addition of immunosuppressive drugs) [18]. Although our patient received a combination of high-dose intravenous corticosteroids and immunoglobulin, his condition worsened, and he passed away due to respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, anti‐MDA5‐Ab‐positive DM patients with RP‐ILD are treated with intensive immunosuppressive therapy as induction therapy that includes high‐dose prednisone, tacrolimus and IVCY. These intensive immunosuppressive therapies increaseed the survival rate of these patients . After induction therapy, DM patients with anti‐MDA5‐Ab are treated with low‐dose prednisone and tacrolimus as maintenance therapy; however, some patients may show flare‐up with an increase in anti‐MDA5‐Ab level during maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These intensive immunosuppressive therapies increaseed the survival rate of these patients. 33 After induction therapy, DM patients with anti-MDA5-Ab are treated with low-dose prednisone and tacrolimus as maintenance therapy; however, some patients may show flare-up with an increase in anti-MDA5-Ab level during maintenance therapy. Thus, adding BAFF inhibition therapy may be an ideal treatment strategy for maintenance therapy in these patients.…”
Section: Serum Baff Levels (Ng/ml)mentioning
confidence: 99%